Endometriosis Nodule Causing Spontaneous Haemoperitoneum in Pregnancy: A Case Report and Literature Review - Junaid Rafi; Geetha Mahindrakar; Debjani Mukhopadhyay (Hindawi Limited, 2017)
Spontaneous haemoperitoneum in pregnancy (SHiP) due to endometriosis is a very rare condition and this is a case of a 41-year-old primigravida, who presented at 32 weeks with sudden onset of severe lower abdominal pain without any uterine activity. This was a dichorionic-diamniotic twin pregnancy, following in vitro fertilisation for subfertility secondary to severe endometriosis. On admission, pain score was eight, with ten being the maximum of the scale. The vital signs were stable. Abdominal palpation revealed generalised tenderness with no guarding or palpable contraction. There was no evidence of bleeding and the cervical os was closed on speculum examination. The cardiotocograph (CTG) was pathological and a plan was made to deliver the babies with emergency caesarean section. Intraoperatively, there was massive haemoperitoneum which was managed successfully with the involvement of multidisciplinary input from general surgeons and urologists with optimum maternal and fetal outcome.